2021
DOI: 10.1002/lio2.697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transducer placements on thresholds in ears with an abnormal ear canal and severe conductive hearing loss

Abstract: Objectives Providing hearing compensation to patients with aural atresia is considerably challenging. Hearing aid transducers vibrating the aural cartilage (cartilage conduction; CC) have been devised, and hearing aids utilizing them (CC hearing aids) have quickly become a beneficial option for aural atresia in clinical applications. However, it remains unclear which placement (on the aural cartilage or mastoid) is beneficial to signal transmission. Methods This study included 35 patients (53 ears with an abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In cases with fibrotic aural atresia, fibrotic tissue may be connected to the ossicles. Sound can travel to the cochlea via these fibrotic tissues and ossicles (fibrotic tissue pathway) without skull bone vibration, which achieves excellent benefits from CC hearing devices [27,28]. In this study, there was no fibrotic tissue pathway in four ears.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In cases with fibrotic aural atresia, fibrotic tissue may be connected to the ossicles. Sound can travel to the cochlea via these fibrotic tissues and ossicles (fibrotic tissue pathway) without skull bone vibration, which achieves excellent benefits from CC hearing devices [27,28]. In this study, there was no fibrotic tissue pathway in four ears.…”
Section: Discussionmentioning
confidence: 62%
“…CC hearing devices have better aided hearing levels than ADHEAR [19], which may result from the difference not only in the transducer output, but also place of fixation, thickness of the fixation tape, and mass of the transducer. Regarding the fixation place, the thresholds for cartilage stimulation are better than those for mastoid stimulation at low frequencies when the simple-type transducer is used [28]. In ADHEAR and CC hearing devices with simple-type transducers, the surface of the transducer in contact with the body is regular.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the vibrator placed on the mastoid, the delivered vibrations could deteriorate because they are delivered to the skull bone via the cartilaginous tissues. A previous study compared the thresholds of a vibrator on the aural cartilage and those on the mastoid (cartilage and mastoid stimulation conditions) [ 32 ]. A previous study demonstrated the thresholds at low frequencies to be significantly better in the cartilage stimulation condition, and that no difference was present in the thresholds at high frequencies, implying that the fixation placement had no negative effect.…”
Section: Signal Transmission Pathway To the Cochlea In Atretic Earsmentioning
confidence: 99%
“…The findings demonstrated an improvement in the thresholds of the fibrotic pathway, and the benefits became more significant as the frequency decreased. In another study, the thresholds in atretic ears with a fibrotic pathway significantly improved by approximately 20 dB at frequencies below 1000 Hz when the transducer was placed on the aural cartilage [ 32 ]. No differences were observed in the thresholds at frequencies above 2000 Hz.…”
Section: Benefits Of CC In Atretic Ears With Fibrotic Pathwaysmentioning
confidence: 99%
“…This means that the BC sensitivity from the contribution of skull bone vibrations alone is nearly the same at the two positions, which is also suggested by the cochlear promontory simulations in Figure 5. This finding is corroborated by the results in Nishimura et al (2021) where ears suffering from aural atresia had a similar threshold independent of whether the transducer was applied at the mastoid or at the ear canal opening.…”
Section: Skull Bone Vibrationsmentioning
confidence: 99%